Pengaruh Media Loose Part Terhadap Prososial Anak Usia Dini - Patrio Malailehi; Densi Oktavia Bekamalai; Adris Imelda Tabais; Nelci Karel; Esmida Delfiani Betty; Debora Madde; Agnes Meka; Yohanes Lanalo; Yunita Banunaek; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Prosocial development is very important for early childhood. One learning method to stimulate children's prosocial development is the use of loose parts media as a strength that forms the basis for the development of creativity, memory stages, group cooperation, vocabulary absorption, concepts of family relationships, self-control, special skills, affection, and cognitive skills. This study aims to determine the effect of loose parts media on the prosocial development of children aged 4-6 years at TK Tunas Baru, Nunkurus Village, East Fatuleu District, Kupang City. This study used quantitative methods. Data collection tools used psychological scales with role playing scale instruments and Child Social Development Scale instruments. The respondents in this study were 20 children aged 4-6 years using a total sampling technique in one PAUD in Nunkurus Village. Data analysis techniques used simple linear regression analysis. The results of this study prove that loose parts media has a positive and significant effect on the prosocial development of children aged 4-6 years by 74%. It is hoped that educators can stimulate children with the loose parts media method so as to improve the prosocial development of early childhood.